RELEVANCE OF MINIMAL RESIDUAL DISEASE FOR HEMATOPOIETIC STEM CELL TRANSPLANTATION IN ACUTE MYELOID LEUKEMIA: AN OVERVIEW - Furtado, Felipe Magalhães (JOURNAL OF BONE MARROW TRANSPLANTATION AND CELLULAR THERAPY, 2021)
Minimal residual or measurable disease (MRD) can predict relapse in AML patients. Depending on patients` risk stratification, MRD status may indicate that the patient will benefit from autoSCT and alloSCT in first clinical remission. In case of persistent MRD positivity, there is no consensus on whether there are benefits to perform additional consolidation treatments to eradicate MRD before alloSCT. Anyway, the persistence of pre-transplant MRD does not contraindicate alloSCT, but indicates an urgent need for transplantation, in addition to being considered a strong independent predictor of posttransplant outcomes in AML. Currently two approaches can be used to detect MRD in clinical practice, multiparameter flow cytometry (MFC) and real time PCR (RT-qPCR), although more sensitive new technologies are emerging, such as digital droplet PCR and next generation sequencing (NGS). Despite the differences of each distinct methodology available, MRD monitoring is currently part of the standard of care for AML patients.